MENNESKER OG ELEFANTER: Om tolkninger af Afrikas elefanter i Afrika og Europa - Svennevig, Ingeborg (Tidsskriftet Antropologi, 1996)
Ingeborg Svennevig: People and elephants - Of interpretations of African elephants in Africa and Europe In the article the author ventures into the different interpretations that people have made of the African elephant. These are then interpreted as being founded on three distinet perception of the relation between people and animals: Anthropocentric, anthropomorphic and zoomorphic. Examples are then given of the relations between people and elephants in accordance with the perceptions. Firstly, as an animal meant for utilisation by people primarily being hunted for ivory and meat. Secondly, as an animal that people can understand as they do each other, and therefore hunt it in special ways that seems acceptable for the hunter. And thirdly, as an animal that can funetion as an exemplary to people and the way we are living together in a natural environment. It is concluded that animals should only funetion as exemplary for people, when it is stressed that the exempla- ry is of human origin, carrying cultural and/ or social prescriptions.